Born again and beyond - Harvey, John E., 1965- (Cascade Books; Eugene, Oregon, 2014)
Description: Born Again and Beyond identifies and interacts with various theological blind spots in Evangelicalism--such as its naive rationality, its faulty understanding of the nature of both Scripture and the gospel, and its emphasis on salvation as an event rather than a process. At the same time, Born Again and Beyond recognizes the real goodness that evangelicalism has brought to the world. Whether it be caring for the outcast and underprivileged, or insisting that one can have a personal relationship with God in Christ, Evangelicalism has certainly played a key role in the advancement of the Kingdom of God in modern times. Perhaps the most destructive element of Evangelicalism has been the equating of it with the gospel itself. Like other expressions of authentic Christian faith, Evangelicalism must not regard itself as the principal locus of the gospel. Having been an Evangelical for decades, John E. Harvey comes to this discussion not as a misinformed outsider, but as one who has sympathy with the Evangelical cause.
Keywords: Evangelicalism